2010
DOI: 10.1097/mej.0b013e328320ad48
|View full text |Cite
|
Sign up to set email alerts
|

Acute cardiac effects of carbon monoxide poisoning in children

Abstract: Myocardial injury may exist in children with CO poisoning without abnormal ECG findings. GCS score

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 13 publications
2
39
0
1
Order By: Relevance
“…In our study, the level of COHb was found to be above 30% in the patients who presented with loss of consciousness and seizure. The mean GCS score was found to be 13.8±2.5 in the study performed by Kandiş et al (9) reported that patients with hypotension have more severe clinical signs and lower GCS score (6). GCS was found to be <14 in 4.6% of the patients in our study group.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In our study, the level of COHb was found to be above 30% in the patients who presented with loss of consciousness and seizure. The mean GCS score was found to be 13.8±2.5 in the study performed by Kandiş et al (9) reported that patients with hypotension have more severe clinical signs and lower GCS score (6). GCS was found to be <14 in 4.6% of the patients in our study group.…”
Section: Discussionmentioning
confidence: 53%
“…Children become symptomatic earlier in CO poisoning, since they have less blood volume, faster basal metabolism and higher tissue oxygen requirement and they are more sensitive to the toxic effects of CO (6). Clinically, CO poisoning can present with a wide spectrum of manifestations ranging from mild compliants to fainting, seizure and coma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myocardial injury may exist in children with CO poisoning, therefore electrocardiogram and cardiac enzymes should be obtained. If abnormal, a cardiac echocardiogram should be obtained [ 206 ].…”
Section: Carbon Monoxidementioning
confidence: 99%
“…Les enfants sont également victimes d'atteinte myocardique comme le confirme une étude récente [21]. Les enfants ayant un taux d'HbCO inférieur à 10 % ont eu un dosage de troponine Ic.…”
Section: Physiopathologieunclassified